Determining the Components of the Excellence Model in Educational Development and Human Resource Development in the Zahedan Education Organization - Hormozi moghaddam, Farzaneh; saffarian Hamedani, Saeid; Uosefi Saeedabadi, Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this research was to determine the components of the excellence model in educational development and human resource development in the Zahedan Education Organization. Method: The research method was applied in terms of objective and qualitative in terms of research methodology. The research population consisted of selected experts from the Zahedan Education Organization with experience in management and policy-making, who were determined purposively based on theoretical saturation to a number of 17 individuals. The method of data collection was through library research, and the measurement tool was semi-structured interviews. In this plan, the stages of analyzing the collected qualitative data were conducted in two stages: open coding and axial coding. Results: The results showed that the dimensions of the excellence model in educational development and human resource development in the Zahedan Education Organization were divided into five aspects: causal factors, contextual factors, intervening factors, strategic factors, and outcomes. The components identified were 1. Equity 2. Financial resources (inputs), 3. Efficiency and management in the dimension of causal factors; and the components 1. Effective management in the organization 2. Legal support for innovation in staff training 3. Resource capacities in the dimension of contextual factors; and the components 1. Managerial weaknesses 2. Procedural barriers 3. Legal and regulatory obstacles in the dimension of intervening factors; and the components 1. Increasing economic capacities and financial support 2. Development of educational capacities 3. Increasing agility in the dimension of strategic factors; and the components 1. Improving employee performance 2. Developing employee participation 3. Sustainable development in the dimension of outcomes were identified. Conclusion: Given the obtained results, it was suggested that the Zahedan Education Organization should act gradually and step by step towards the realization of these categories, considering a roadmap and a long-term strategic plan. The development of an operational plan is necessary to implement it. Having a paradigmatic approach with a local and regional perspective also helps its realization.